Learning Strategies for E-Learning In Primary Schools Through Use of Zoom Meeting Technology in the Covid-19 Pandemic Era - Herdin Muhtarom (Future Science, 2021)
Abstract:During the Covid-19 pandemic, all learning activities were carried out through technology-based learning media, to avoid the spread of the Covid-19 virus. The purpose of this study was to find out how E-learning learning strategies in elementary schools through the use of Zoom Meeting technology in the era of the Covid-19 pandemic. The method in this research is to use the library research model (Library Research). The results showed that the learning media using Zoom Meeting technology as the most effective learning media used during learning in elementary schools, because it provides convenience in face-to-face interaction with teachers and peers. Keywords: Zoom Meeting, Learning Strategies, Learning Media